An optical watermarking solution for authenticating printed document - SUN, Q. B. (Institutional Knowledge at Singapore Management University, 2001)
We present a novel and simple optical watermarking system aiming at overriding some practical problems when the state-of-the art digital watermarking techniques are applied to authenticate printed documents. We name our technique optical watermarking differing from traditional digital watermarking in the sense that the watermark extraction is done by some optical and visual means like a photocopier, while no digitization is required. The system security is guaranteed by adopting a content-based key share scheme originated from visual cryptography. The non-obtrusiveness effect of the watermarked document is achieved by modulating the watermark into a higher resolution grating level. Experimental results demonstrate the availability and practicality of the proposed approach.